Identification, characterization, and immunological analysis of complement component 4 from grass carp (Ctenopharyngodon idella). Issue 104 (September 2020) - Meng, Xin-Zhan; Wang, Shen-Tong; Xu, Xiao-Yan; Dang, Yun-Fei; Zhang, Meng; Zhang, Jia-Hua; Wang, Rong-Quan; Shen, YuBang; Li, Jia-Le
Abstract: Complement component 4 (C4) has critical immunological functions in vertebrates. In the current study, a C4 homolog ( gcC4 ) was identified in grass carp ( Ctenopharyngodon idella ). The full-length 5458 bp gcC4 cDNA contained a 5148 bp open reading frame (ORF) encoding a protein of 1715 amino acids with a signal peptide and eight conservative domains. The gcC4 protein has a high level of identity with other fish C4 counterparts and is phylogenetically clustered with cyprinid fish C4. The gcC4 transcript shows wide tissue distribution and is inducible by Aeromonas hydrophila in vivo and in vitro . Furthermore, its expression also fluctuates upon lipopolysaccharide or flagellin stimulation in vitro . During infection, the gcC4 protein level decreases or increases to varying degrees, and the intrahepatic C4 expression location changes. With gcC4 overexpression, interleukin 1 beta, tumor necrosis factor alpha, and interferon transcripts are all upregulated by A. hydrophila infection. Meanwhile, overexpression of gcC4 reduces bacterial invasion or proliferation. Moreover, gcC4 may activate the NF-κB signaling pathway. These findings demonstrate the vital role of gcC4 in the innate immunity of grass carp. Highlights: A C4 homolog ( gcC4 ) is identified in grass carp ( Ctenopharyngodon idella ). gcC4 mRNA or protein expression is induced by A. hydrophila or PAMPs. Overexpression of gcC4 inhibits the invasion and proliferation of A. hydrophila. Overexpression of gcC4 induces the expression of immune-related genes. Overexpression of gcC4 activates the NF-κB signaling pathway.